Profesor Yi Lijun - Gang, Zhao (Postscriptum Polonistyczne, 2020)
The article presents Yi Lijun’s translation and academic activity. Yi Lijun is a professor at the Polish Philology Faculty at Beijing Foreign Studies University and a translator of Polish literature into Chinese. She began her scholarly pursuit in this area in 1962 after graduating a university in Poland. During 50 years of this work she educated close to 200 graduates of Polish Philology Faculty. An important contribution of Professor Lijun is promoting among Chinese readers the canon of Polish literature as well as some important contemporary works. Yi Lijun has translated into Chinese works of Mickiewicz, Sienkiewicz, Gombrowicz. She is also an author of numerous critical works concerning Polish literature. Professor Yi Lijun’s merits have been highly appreciated by Chinese and Polish governments.